2018
DOI: 10.3892/or.2018.6939
|View full text |Cite
|
Sign up to set email alerts
|

Pilot investigation of the mutation profile of PIK3CA/PTEN genes (PI3K pathway) in grade 3 endometrial cancer

Abstract: Endometrial cancer (EC) comprises a biological and clinical heterogeneous group of tumors. Several genetic alterations are involved in the development and progression of EC, and may be used for targeted therapy, particularly in patients with advanced-stage EC. In the present study, a combined procedure was developed based on polymerase chain reaction (PCR)-high resolution melting analysis (HRMA) and Sanger sequencing for the evaluation of somatic mutations in selected phosphoinositide 3-kinase (PI3K) catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Hereby, the remarkable overall genetic alterations of PI3K/AKT pathway are shown in EC, such as: PIK3CA (34%), PIK3R1 (19%), PIK3R2 (5%), AKT1 (3%) and AKT2 (5%), especially PTEN (32%, Table 1). What's more, it's revealed that the majority of the G3 EEC samples have exhibited PIK3CA mutations (39%) and PTEN mutations (67%) [227]. Moreover, JQ1, NEDD4, PDCD4, miR-101, -494-3p, Lnc RNA LINP1 and MEG3 have shown their aptitudes for controlling tumorigenesis, proliferation, apoptosis, invasion, progression of EC cells via PI3K/AKT pathway [228][229][230][231][232][233][234].…”
Section: Nct02240212mentioning
confidence: 99%
“…Hereby, the remarkable overall genetic alterations of PI3K/AKT pathway are shown in EC, such as: PIK3CA (34%), PIK3R1 (19%), PIK3R2 (5%), AKT1 (3%) and AKT2 (5%), especially PTEN (32%, Table 1). What's more, it's revealed that the majority of the G3 EEC samples have exhibited PIK3CA mutations (39%) and PTEN mutations (67%) [227]. Moreover, JQ1, NEDD4, PDCD4, miR-101, -494-3p, Lnc RNA LINP1 and MEG3 have shown their aptitudes for controlling tumorigenesis, proliferation, apoptosis, invasion, progression of EC cells via PI3K/AKT pathway [228][229][230][231][232][233][234].…”
Section: Nct02240212mentioning
confidence: 99%
“…PIK3CA mutations have been reported in urothelial papilloma cases [111]. PIK3CA gene amplification has been observed in recurrent ovarian cancer [112] and yolk sac tumors [113]. In addition, PIK3CA mutation was identified in 38% endometrial cancer samples [114].…”
Section: Association Of Pik3ca Genetic Mutations With Cervical Ovarimentioning
confidence: 99%
“…UCSC disrupts a lot of signal pathways including PI3K/PTEN/AKT/mTOR pathway [3]. PI3K pathway serves a pivotal function that may have potential for defining targeted therapy for the treatment of grade 3 UCEC [4]. The main component of PI3K pathway, PIK3CA, is a strong prognostic biomarker in UCEC and associates with disease-specific mortality [5].…”
Section: Introductionmentioning
confidence: 99%